1959
DOI: 10.1680/geot.1959.9.2.33
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies of the Properties of London Clay

Abstract: Synopsis A number of physical and mechanical properties of the London Clay are given based on observations made in several tunnel excavations, and from laboratory tests on specimens. These specimens have been carefully prepared by hand trimming from blocks of clay, which were extracted from tunnels over a large area of the London Basin. Earlier studies of someof these properties (Cooling and Skempton, 1942; Bishop, 1947; Skempton and Henkel, 1957)have been restricted to measurements on samples obtained from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The influence of the fissured fabric of London clay on undrained and drained strength has received a great deal of attention (Ward et al, 1959;Bishop, 1966;Marsland and Butler, 1967;Skempton and Hutchinson, 1969) and an examination of fissure spacing and orientation is an essential preliminary step towards representative sampling and testing. The very thorough examination of the joints and fissures at Wraysbury by demonstrated an absence of permeable fabric at that location.…”
Section: Eocenementioning
confidence: 99%
“…The influence of the fissured fabric of London clay on undrained and drained strength has received a great deal of attention (Ward et al, 1959;Bishop, 1966;Marsland and Butler, 1967;Skempton and Hutchinson, 1969) and an examination of fissure spacing and orientation is an essential preliminary step towards representative sampling and testing. The very thorough examination of the joints and fissures at Wraysbury by demonstrated an absence of permeable fabric at that location.…”
Section: Eocenementioning
confidence: 99%
“…The stress history to which London Clay has been subjected would be expected to have developed marked anisotropy and we find this to be the case. Ward, Samuels and Butler in their paper (Ward et al, 1959). The sites extend from Hampstead to Stockwell and from Walton to the City.…”
mentioning
confidence: 99%
“…There was a good deal of evidence (for London Clay see Skempton and Henkel, 1957;Ward, et al, 1959Ward, et al, , 1965 Two extreme cases can be identified (a) x=0 (b) E(0) =o. The first of these is the ctassical case and would provide a useful check of the general analysis.…”
mentioning
confidence: 99%
“…(Gazetas, 1982;Kirkpatrick & Rennie, 1972;Kirkgard & Lade, 1991). Heavily overconsolidated clays may develop a strong anisotropic behaviour, with reported typical values of n ranging from 1.35 to 2.4 (Ward, Samuels & Gutler, 1959;Atkinson, 1975;Gerrard, 1977) whereas desiccated clays have shown values of I? from 1.8 to 4.2 (Gazetas, 1981).…”
Section: Methodsmentioning
confidence: 99%